Electrophotographic member, fixing device, and electrophotographic image forming apparatus
The laminated structure of the electrophotographic member with specific resistivity layers and an ion conductive resin layer addresses electrostatic offset, ensuring stable and high-quality image formation by charge neutralization.
Patent Information
- Application Number
- JP2023201842
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-27
- Filing Date
- 2023-11-29
- Publication Date
- 2025-01-16
AI Technical Summary
Existing electrophotographic fixing members experience electrostatic offset due to the fluororesin layer becoming negatively charged during the imaging process, leading to unfixed toner adhering to the release layer, which affects the quality and stability of electrophotographic images.
The electrophotographic member is designed with a laminated structure comprising a base layer, an elastic layer with a surface resistivity of 1×10^14 Ω/□ or more, a resin layer containing an ion conductive agent with a resistivity of 1×10^14 Ω/□ or more, and a surface layer with a resistivity of 1×10^15 Ω/□ or more, which neutralizes charges through charge relaxation without relying on ion conductive agents in the surface layer.
This configuration effectively prevents electrostatic offset, ensuring stable formation of high-quality electrophotographic images by neutralizing charges within the member, thereby improving image quality and durability.
Smart Images

Figure 2025005361000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic member used in a fixing device of an electrophotographic image forming apparatus, and to a fixing device and an electrophotographic image forming apparatus including the electrophotographic member. [Background technology]
[0002] Fixing members used in the fixing devices of electrophotographic image forming apparatuses such as printers, copiers, and facsimiles are available in the form of films or rollers. These fixing members include a fixing member having a heat-resistant resin or metal film or roller-shaped base material made of heat-resistant resin or metal, an elastic layer on the base material, and a release layer on the elastic layer. Here, the release layer often contains a fluororesin that has excellent releasability against toner.
[0003] Fluorine resin is most likely to be negatively charged in the triboelectric series, and therefore, when the outer surface of the fixing member, i.e., the outer surface of the release layer, rubs against paper or a pressure member during the process of forming an electrophotographic image, the release layer of the fixing member becomes charged, and electrostatic offset occurs in which unfixed toner electrostatically adheres to the release layer of the fixing member. Patent Document 1 discloses a fixing device having a fixing member, the surface material of which contacts a toner image contains at least a fluororesin and an ion-conductive electrical resistance control material having a melting point equal to or higher than the maximum operating temperature of the fixing device, and describes that such a fixing device can prevent the occurrence of electrostatic offset. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 08-220907 Summary of the Invention [Problem to be solved by the invention]
[0005] At least one aspect of the present disclosure is directed to providing an electrophotographic member capable of stably exerting an effect of preventing electrostatic offset. At least one aspect of the present disclosure is directed to providing a fixing device that contributes to the stable formation of high-quality electrophotographic images. Furthermore, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images. [Means for solving the problem]
[0006] According to at least one aspect of the present disclosure, there is provided an electrophotographic member having at least a base layer, an elastic layer, and a surface layer containing a fluororesin, in this order, comprising: The surface resistivity of the elastic layer is 1×10 14 Ω / □ or more, The surface resistivity of the surface layer is 1×10 15 Ω / □ or more, the electrophotographic member further comprises a resin layer between the elastic layer and the surface layer, The resin layer contains an ion conductive agent, and The surface resistivity of the resin layer is 1×10 14 Electrophotographic members are provided having a resistivity of Ω / □ or greater.
[0007] According to at least one aspect of the present disclosure, there is provided a fixing device in an electrophotographic image forming apparatus, the fixing device comprising a fixing member and a pressure member disposed opposite the fixing member, and at least one of the fixing member and the pressure member being the electrophotographic member described above.
[0008] According to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including a fixing device. The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, and at least one of the fixing member and the pressure member is the electrophotographic member described above, thereby providing an electrophotographic image forming apparatus. Effect of the Invention
[0009] According to at least one aspect of the present disclosure, a fixing member capable of stably exhibiting the effect of preventing electrostatic offset can be obtained. Also, according to at least one aspect of the present disclosure, a fixing device contributing to the stable formation of high-quality electrophotographic images can be obtained. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images can be obtained. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic diagram of an image forming apparatus according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram of a fixing device according to an embodiment of the present disclosure. [Diagram 3] 1 is a cross-sectional view of a fixing belt according to an embodiment of the present disclosure. [Figure 4] FIG. 2 is an explanatory diagram of a charge potential measuring device. [Diagram 5] 4A to 4C are diagrams illustrating the effect of preventing electrostatic offset achieved by an electrophotographic member according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In this specification, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower limit and the upper limit, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In this disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. In addition, in this disclosure, "Ω / □" is a unit of surface resistivity defined in Japanese Industrial Standards (JIS) K6911:2006, and is synonymous with "Ω / square".
[0012] When the present inventors studied the fixing member according to Patent Document 1, they found that the effect of preventing electrostatic offset was not sufficient in some cases. The reason for this is believed to be that the effect of preventing electrostatic offset of the fixing member according to Patent Document 1 is based on the ionic conductive agent in the surface layer of the fixing member, and the amount of the ionic conductive agent in the surface layer is reduced or lost due to bleeding to the surface of the surface layer. Therefore, the present inventors have repeatedly studied to obtain a fixing member that can stably prevent electrostatic offset by a method other than containing an ionic conductive agent in the surface layer. As a result, they have found that a fixing member having the following configuration can prevent electrostatic offset without containing an ionic conductive agent in the surface layer.
[0013] <Configuration> An electrophotographic member having at least a base layer, an elastic layer, and a surface layer containing a fluororesin in this order, wherein the surface resistivity of the elastic layer is 1×10 14 Ω / □ or more, and the surface resistivity of the surface layer is 1×10 15 Ω / □ or more, the electrophotographic member further has a resin layer between the elastic layer and the surface layer, the resin layer contains an ion conductive agent, and The surface resistivity of the resin layer is 1×10 14 Electrophotographic member having a resistivity of Ω / □ or more.
[0014] A fixing member and an image forming apparatus according to one embodiment of the present disclosure will be described with reference to the drawings, but the fixing member according to the present disclosure is not limited to the configuration embodied in this embodiment.
[0015] <Fixing material> The electrophotographic member according to one embodiment of the present disclosure may be, for example, a fixing rotating body such as a fixing roller or a fixing belt (fixing film). Hereinafter, the fixing member will be described by taking as an example an electrophotographic member having an endless shape (hereinafter, simply referred to as an "electrophotographic belt").
[0016] The fixing film 41 according to this embodiment shown in FIG. 3 has a base layer 41d, an elastic layer 41c covering the outer surface thereof, and a surface layer 41a covering the surface of the elastic layer opposite to the side facing the base layer. The surface layer 41a constitutes the outer surface of the electrophotographic member, and can be a release layer having releasability against, for example, toner. In addition, a resin layer 41b is provided as an adhesive layer on the surface of the elastic layer 41c opposite to the side facing the base layer, that is, between the surface layer 41a and the elastic layer 41c. The resin layer 41b contains an ion conductive agent. Here, the resin layer 41b may be a single layer or a laminate of multiple layers. However, from the viewpoint of more reliably exerting the charge neutralizing effect of the resin layer 41b described later, it is preferable that the resin layer 41b is a single layer. When the resin layer 41b is a laminate of multiple layers, the laminate may include an adhesive layer and other layers, and the ion conductive agent may be contained in at least one of the multiple layers constituting the laminate.
[0017] The present inventors speculate as follows why the electrophotographic member according to the present disclosure can prevent electrostatic offset despite having a laminated structure of a surface layer 41a having a high surface resistivity and an elastic layer 41c having a high surface resistivity.
[0018] As shown in FIG. 5, in the fixing process of an electrophotographic image, when the outer surface of the surface layer 41a is rubbed by the movement of the recording material P in the direction of the arrow 505, the vicinity of the surface 41a-S of the surface layer 41a in contact with the recording material P is negatively charged, and the surface side opposite to the surface 41a-S of the surface layer 41a is positively charged. Then, in response to the polarization in the surface layer 41a, the anions of the ion conductive agent in the resin layer 41b move to the side closer to the surface layer 41a, and the cations move to the side of the resin layer 41b away from the surface layer 41a. As a result, it is considered that the negative charge generated on the surface 41a-S side of the surface layer 41a is alleviated by the cations polarized in the resin layer 41b, and the charge is neutralized in the entire electrophotographic member.
[0019] The correctness of the above-mentioned charge neutralization mechanism is considered to be evident from the following experimental results. The present inventors prepared the following electrophotographic belt as an electrophotographic belt according to the present disclosure. The belt has a laminated structure of a base layer 41d, an elastic layer 41c on the base layer, a resin layer (adhesive layer) 41b containing an ion conductive agent, and a surface layer 41a, and the surface resistivity of the elastic layer is set to 1×10 14 Ω / □, and the surface resistivity of the surface layer is 1×10 15 Ω / □, and the surface resistivity of the resin layer is 1×10 14 The ratio was set to Ω / □. After the outer surface 41a-S of this electrophotographic belt was neutralized, a grid part of a corona discharger was placed with a gap of 10 mm from the outer surface, and a voltage of -5 kV was applied to the corona discharger for 15 seconds. The potential of the outer surface was measured at 0.1 second intervals starting from the point (0 seconds) when the voltage application to the corona discharger was stopped. As a result, the highest potential was -620 V 10 seconds after the discharge was stopped.
[0020] On the other hand, the same measurement was carried out on an electrophotographic belt as a control example, in which the resin layer 41b did not contain an ion conductive agent. As a result, the highest potential of the electrophotographic belt as the control example was −750 V 10 seconds after the discharge was stopped.
[0021] That is, it was found that the outer surface 41a-S of the surface layer of the electrophotographic belt according to the present disclosure was difficult to be charged, even though the surface layer and the elastic layer were insulating. From this, it was found that the effect of preventing electrostatic offset achieved by the fixing member according to the present disclosure is not obtained by dissipating the charge of the surface layer, but by charge neutralization (charge relaxation). It is believed that this is the case.
[0022] In addition, as described above, the electrophotographic belt according to the present disclosure utilizes the charge neutralizing effect by including an ion conductive agent in the adhesive layer. Therefore, the ion conductive agent is unlikely to bleed onto the surface 41a-S of the surface layer 41a. Therefore, the amount of the ion conductive agent in the adhesive layer is unlikely to fluctuate, and the effect of preventing electrostatic offset can be stably obtained.
[0023] Each layer will be specifically described below. <base layer> The material of the base layer 41d is not particularly limited and may be any known electrophotographic material. For example, metals and alloys such as aluminum, iron, stainless steel (SUS), and nickel, and heat-resistant resins such as polyimide are used. Stainless steel is preferable. The thickness of the base layer 41d is not particularly limited, but is preferably 20 μm to 100 μm, more preferably 20 μm to 50 μm, from the viewpoints of strength, flexibility, and heat capacity.
[0024] The outer surface of the base layer 41d may be subjected to a surface treatment to impart adhesion to the elastic layer 41c. The surface treatment may be one or a combination of physical treatments such as blasting, lapping, and polishing, and chemical treatments such as oxidation, coupling agent, and primer treatment.
[0025] When the elastic layer 41c containing silicone rubber is provided on the surface of the base layer 41d, it is preferable to perform a primer treatment on the surface of the base layer 41d in order to improve the adhesion between the base layer 41d and the elastic layer 41c. Examples of the primer used in the primer treatment include paints in which a silane coupling agent, a silicone polymer, hydrogenated methylsiloxane, an alkoxysilane, a reaction accelerating catalyst, and a coloring agent such as red iron oxide are appropriately mixed and dispersed in an organic solvent.
[0026] The primer can be appropriately selected depending on the material of the base layer 41d, the type of the elastic layer 41c, or the form of the crosslinking reaction. In particular, when the elastic layer 41c contains a large amount of unsaturated aliphatic groups such as vinyl groups, a primer containing a hydrosilyl group is preferably used to impart adhesiveness by reacting with the unsaturated aliphatic groups. Also, when the elastic layer 41c contains a large amount of hydrosilyl groups, a primer containing an unsaturated aliphatic group such as vinyl groups is preferably used.
[0027] Other examples of the primer include those containing an alkoxy group. A commercially available primer can be used. The primer treatment includes a step of applying the primer to the outer surface of the base layer 41d (the surface to be bonded to the elastic layer 41c) and drying or baking the primer.
[0028] <Elastic layer> The surface resistivity of the elastic layer 41c is 1×10 14 When the elastic layer 41c contains the above-mentioned filler, the surface resistivity of the elastic layer is 1×10 14 The elastic layer contains a filler, so its surface resistivity is 1×10 14 If the surface resistivity is less than Ωcm, current leakage due to the aggregation of the filler may occur, which may cause defects in the electrophotographic image. 14 ~1×10 16 Ω / □ is preferred.
[0029] The thickness of the elastic layer 41c can be appropriately designed, for example, taking into consideration the hardness of the surface of the electrophotographic member and the width of the nip portion formed between the electrophotographic member and a member disposed opposite the electrophotographic member. When the electrophotographic member is used as the fixing member, the thickness of the elastic layer 41c is preferably 100 μm to 3000 μm, more preferably 200 μm to 400 μm. Elastic By setting the layer thickness within the above range, a fixing nip portion of sufficient width can be secured when the electrophotographic member is incorporated as a fixing member in a fixing device. In addition, by setting the thickness of the elastic layer to 100 μm or more, the outer surface of the electrophotographic member can be made to better follow the unevenness of the paper surface. This makes it easier to further improve the fixing and thermal conductivity of the unfixed toner image to the paper.
[0030] The elastic layer 41c may be made of any material known in the electrophotographic material, and is not particularly limited. The elastic layer 41c preferably contains silicone rubber having excellent heat resistance. In addition, an addition-curing liquid silicone rubber mixture is preferably used as the raw material for the silicone rubber. That is, the elastic layer 41c preferably contains a cured product of the addition-curing liquid silicone rubber mixture. Such an elastic layer can be formed, for example, by forming a coating of the addition-curing liquid silicone rubber mixture on the outer surface of the base layer 41d, and heating and curing the coating.
[0031] An embodiment of an addition-curing liquid silicone rubber mixture that can be used to form the elastic layer 41c will be described in detail below. The addition-curing liquid silicone rubber mixture contains at least the following components (a) to (c) and optionally contains the following component (d): Component (a): an organopolysiloxane having an unsaturated aliphatic group; Component (b): an organopolysiloxane having active hydrogen bonded to silicon; Component (c): catalyst; Ingredient (d): Filler.
[0032] Each component will be described below. Component (a) The organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and examples thereof include those shown in the following structural formulas (1) and (2). The organopolysiloxane having an unsaturated aliphatic group is preferably a linear type. [ka]
[0033] In structural formula (1), m 1 is an integer equal to or greater than 0, and n 1 represents an integer of 3 or more. In addition, in the structural formula (1), R 1 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R1 At least one of R represents a methyl group. 2 each independently represents an unsaturated aliphatic group. [ka]
[0034] In structural formula (2), n 2 denotes a positive integer, and R 3 each independently contains an unsaturated aliphatic group represents a monovalent unsubstituted or substituted hydrocarbon group that is not 3 At least one of R represents a methyl group. 4 each independently represents an unsaturated aliphatic group.
[0035] In structural formula (1) and structural formula (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by include the following groups. Unsubstituted hydrocarbon groups Alkyl groups (eg, methyl, ethyl, propyl, butyl, pentyl, hexyl). Aryl groups (eg, phenyl groups). Substituted hydrocarbon groups Substituted alkyl groups (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, 3-methoxypropyl).
[0036] The organopolysiloxanes represented by structural formula (1) and structural formula (2) have at least one methyl group directly bonded to the silicon atom forming the chain structure. However, because of ease of synthesis and handling, R 1 and R 3 It is preferable that 50% or more of each group are methyl groups, and all of R 1 and R 3 More preferably, is a methyl group.
[0037] In addition, in the structural formula (1) and the structural formula (2), R 2 and R 4 Examples of the unsaturated aliphatic group that can be represented by include the following groups. That is, examples of the unsaturated aliphatic group include a vinyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, and a 5-hexenyl group. Among these groups, R 2 and R 4 is preferably a vinyl group.
[0038] From the viewpoint of moldability, the viscosity of component (a) is 1000mm 2 / s or more, 50000mm 2 The viscosity of component (a) is preferably 1000 mm / s or less. 2 When the viscosity is 50,000 mm / s or more, it becomes easier to adjust the addition curing type liquid silicone rubber mixture to a viscosity required for forming the elastic layer 20c. 2 When the viscosity is 1 / s or less, it is possible to more reliably prevent the viscosity of the mixture from becoming too high. The viscosity (kinetic viscosity) can be measured using a capillary viscometer, a rotational viscometer, or the like based on JIS Z 8803:2011.
[0039] The blending amount of component (a) is preferably 55% by volume or more from the viewpoint of durability and 65% by volume or less from the viewpoint of heat conductivity, based on the liquid silicone rubber mixture used to form the elastic layer 20c.
[0040] Ingredient (b) Organopolysiloxanes having active hydrogen bonded to silicon atoms, i.e., organopolysiloxanes having Si-H bonds, function as crosslinking agents that react (hydrosilylation reaction) with the unsaturated aliphatic groups of component (a) under the action of a catalyst to form crosslinked silicone rubber. Any organopolysiloxane having a Si-H bond can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic group of component (a), it is preferable to use one having an average of 3 or more hydrogen atoms bonded to silicon atoms in one molecule.
[0041] Specific examples of component (b) include the linear organopolysiloxane shown in the following structural formula (3) and the cyclic organopolysiloxane shown in the following structural formula (4). [ka]
[0042] In structural formula (3), m 2 is an integer equal to or greater than 0, and n 3 indicates an integer of 3 or more, and R 5 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group. [ka]
[0043] In structural formula (4), m 3 is an integer equal to or greater than 0, and n 4 indicates an integer of 3 or more, and R 6 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.
[0044] R in structural formula (3) and structural formula (4) 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by R 1 Among these, R 5 and R 6 It is preferable that 50% or more of each group are methyl groups, and all of R 5 and R 6 More preferably, is a methyl group.
[0045] Ingredient (c) The catalyst used in forming the silicone rubber may be, for example, a hydrosilylation catalyst for promoting the hydrosilylation reaction. As the hydrosilylation catalyst, for example, a known substance such as a platinum compound or a rhodium compound may be used. The amount of the catalyst to be added may be appropriately set and is not particularly limited.
[0046] Ingredient (d) The elastic layer 41c may contain a filler, which can control, for example, the thermal conductivity, heat resistance, elastic modulus, etc., of the elastic layer. For example, in order to impart high thermal conductivity to the elastic layer, it is preferable to include a thermally conductive filler as component (d) of the addition-curing liquid silicone rubber mixture. Examples of thermally conductive fillers include metals, metal compounds, and carbon fibers. More specifically, examples of fillers include those containing the following materials: Silicon metal (Si), silicon carbide (SiC), silicon nitride (Si3N4), boron nitride (BN), aluminum nitride (AlN), alumina (Al2O3), iron oxide (Fe2O3), zinc oxide (ZnO), magnesium oxide (MgO), titanium oxide (TiO2), silica (SiO2), copper (Cu), aluminum (Al), silver (Ag), iron (Fe), nickel (Ni), carbon black (C), carbon nanotubes (C), vapor grown carbon fiber, PAN (polyacrylonitrile) carbon fiber, pitch-based carbon fiber.
[0047] Other components that may be included in the addition-curing liquid silicone rubber mixture include, for example, a reaction control agent called an inhibitor for controlling the start time of the hydrosilylation reaction. Examples of such reaction inhibitors include methylvinyltetrasiloxane, acetylene alcohols, siloxane-modified acetylene alcohols, and hydroperoxides. An addition-curing liquid silicone rubber composition containing the above components (a) to (c) is, for example, "DOWSIL SE188" which is commercially available as a two-liquid addition reaction curing silicone gel. It can be obtained by mixing solutions A and B of "6" (trade name, manufactured by Dow Toray).
[0048] The surface of the elastic layer 41c is preferably treated with ultraviolet light. This prevents the material for forming a resin layer (adhesive layer) described below from seeping into the elastic layer, and suppresses an increase in hardness of the elastic layer. The ultraviolet light treatment may be performed by a known method. For example, the integrated light amount is preferably 500 to 2000 mJ / cm. 2 , more preferably 600 to 1500 mJ / cm 2 Examples include:
[0049] <Resin layer (adhesive layer)> The resin layer 41b contains an ion conductive agent and has a surface resistivity of 1×10 14 The resistivity is Ω / □ or more. The resin layer 41b may be, for example, a cured product of a mixture of an addition-curing silicone rubber adhesive and an ion conductive agent.
[0050] As described above, the elastic layer preferably contains a cured product of an addition-curing liquid silicone rubber mixture. In that case, the resin layer preferably contains a cured product of an addition-curing silicone rubber adhesive. The addition-curing silicone rubber adhesive has an uncrosslinked component of silicone rubber, and can bond the inside of the surface layer and the uncrosslinked component of the elastic layer by heating. Therefore, the resin layer is preferably a cured product of an addition-curing silicone rubber adhesive containing an ion conductive agent. The addition-curing silicone rubber adhesive can be a commercially available product, such as the two-liquid type "DOWSIL SE1819CV" (trade name, manufactured by Dow Toray).
[0051] The surface resistivity of the resin layer is 1×10 14 The upper limit of the surface resistivity of the resin layer is not particularly limited, but is, for example, 1.0×10 16 The surface resistivity of the resin layer is preferably 1×1014 ~1×10 16 The surface resistivity of the resin layer is preferably 1×10 14 By making the resistivity Ω / □ or more, a polarized state corresponding to the charge on the surface 41a-S of the surface layer 41a can be more effectively generated in the resin layer 41b.
[0052] As the ionic conductive agent, an ionic conductive agent consisting of a combination of a known anion and a known cation can be used, and for example, the ionic conductive agent is not particularly limited and any known ionic conductive agent can be used. The cations and anions constituting the ionic conductive agent are described in detail below.
[0053] <Cation> The cation may be at least one selected from the group consisting of a quaternary ammonium cation such as tributylmethylammonium, an imidazolium cation, a pyridinium cation, and an anion having a siloxane bond in the molecule. Here, when the addition curing type silicone rubber adhesive is used as at least a part of the raw material of the resin layer as described above, the cation is preferably a cation having a siloxane bond in the molecule. The cation having a siloxane bond in the molecule has a high affinity with the organopolysiloxane component contained in the addition curing type silicone rubber adhesive, so that the cation can be uniformly present in the resin layer. As a result, the charge neutralization effect can be more effectively expressed.
[0054] <Anion> The anion may be, for example, a perchlorate anion or a fluorosulfonylimide anion (FSI). , bis(trifluoromethanesulfonyl)imide (TFSI), trifluoromethanesulfonate anion, bis(trifluoromethylsulfonyl)amide, tetrafluoroborate anion, hexafluorophosphate anion, and the like. Among the above anions, TFSI and FSI are preferably used. TFSI has a trifluoromethyl group (CF3) in the molecule. Therefore, TFSI has a large degree of polarization and is advantageous in terms of exerting the charge neutralization effect.
[0055] Furthermore, when an addition-curing silicone rubber adhesive is used as at least a part of the raw material of the resin layer, TFSI exhibits high hydrophobicity due to the presence of trifluoromethyl groups, and the organopolysiloxane in the addition-curing silicone rubber adhesive also exhibits high hydrophobicity. Therefore, the affinity between TFSI and the addition-curing silicone rubber adhesive is high, and as a result, TFSI can be more uniformly present in the resin layer. Therefore, it is believed that it can function more effectively in realizing the charge neutralization effect described above. On the other hand, FSI has a weaker degree of polarization than TFSI. However, since FSI has a smaller molecular size than TFSI, it is considered that FSI has a higher mobility in the resin layer. As a result, it is considered that FSI can function more effectively in realizing the charge neutralization effect described above. Therefore, in the present disclosure, the resin layer preferably includes a cured product of an addition-curing silicone rubber mixture containing an addition-curing silicone rubber adhesive and an ionic conductive agent containing a cation having a siloxane bond in its molecule and at least one anion selected from the group consisting of TFSI and FSI. In particular, the resin layer is preferably a cured product of an addition-curing silicone rubber mixture containing an addition-curing silicone rubber adhesive and an ionic conductive agent containing a cation having a siloxane bond in its molecule and at least one anion selected from the group consisting of TFSI and FSI. In such a resin layer, the ionic conductive agent can be uniformly dispersed in the silicone rubber. In preparing the addition-curing silicone rubber mixture, an ionic conductive agent in which the cation containing the siloxane bond in the molecule and the anion (at least one selected from the group consisting of TFSI and FSI) are paired with each other may be mixed with the addition-curing silicone rubber adhesive, or a first ionic conductive agent consisting of the cation and an anion other than TFSI and FSI, and a second ionic conductive agent consisting of the anion and a cation other than the cation may be mixed with the addition-curing silicone rubber adhesive. In this case, an example of the first ionic conductive agent is "X-40-2750" (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.), which contains a cation having a siloxane bond in the molecule. An example of the second ionic conductive agent is "FC-4400" (trade name, manufactured by 3M Co., Ltd.), which contains TFSI as an anion.
[0056] The content of the ionic conductive agent relative to 100 parts by mass of the resin in the resin layer may be, for example, 0.5 to 31.0 parts by mass, and is preferably 1.0 to 30.0 parts by mass. The resin in the resin layer refers to, for example, a cured product of an addition-curing silicone rubber adhesive. When the content of the ionic conductive agent is within the above range, polarization of the resin layer can be more efficiently generated, and the function as an adhesive layer can be more reliably exerted.
[0057] In particular, when the content of the ionic conductive agent is 1.0 parts by mass or more, the charge neutralization effect is more easily exhibited, and electrostatic offset can be more effectively suppressed. When the content of the ionic conductive agent is 31.0 parts by mass or less, the number of bonds formed between the elastic layer and the resin layer increases. As a result, the peel durability between the elastic layer and the resin layer can be further improved.
[0058] The thickness of the resin layer may be, for example, 0.5 to 6.0 μm, preferably 0.5 to 5.0 μm, and more preferably 1.0 to 5.0 μm. When the thickness of the resin layer is within the above range, not only is electrostatic offset suppressed, but durability is also improved. When the thickness of the resin layer is 0.5 μm or more, it is possible to more sufficiently achieve both the suppression of electrostatic offset and durability. When the thickness of the resin layer is 5.0 μm or less, the charge neutralization effect is more easily exerted, and electrostatic offset can be more effectively suppressed.
[0059] <Surface layer> The surface layer 41a includes, for example, a fluororesin. The surface layer 41a is preferably formed of a fluororesin. There are no particular limitations on the fluororesin, and any known fluororesin may be used. The fluororesin in the surface layer may be, for example, a tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), perfluoropolyether (PFPE), polytetrafluoroethylene (PTFE), or a tetrafluoroethylene-hexafluoropropylene copolymer. At least one selected from the group consisting of FEP and FEP-FEP. The fluororesin preferably contains PFA, and more preferably is PFA. There are no particular limitations on the PFA, and known PFAs can be used. Commercially available PFAs may be used. Specific examples include "Teflon PFA 959HP-PLUS" (product name; manufactured by Mitsui-Chemours Fluoroproducts, Inc.).
[0060] The surface layer containing fluororesin has a surface resistivity of 1×10 15 The upper limit of the surface resistivity is not particularly limited, but is, for example, 1×10 16It is preferable that the resistance is Ω / □ or less. The surface resistivity of the surface layer is, for example, 1×10 15 ~1×10 16 The surface layer preferably has a surface resistivity of 1×10 15 An electronic conductive agent such as carbon black may be contained, provided that the resistivity is Ω / □ or more. However, the inclusion of an electronic conductive agent may cause the surface 4a-S of the surface layer to become rough. In addition, depending on the dispersion state of the electronic conductive agent, the charge in the surface layer may become non-uniform, and the polarization state of the resin layer may become non-uniform. Therefore, it is particularly preferable that the surface layer does not contain an electronic conductive agent. In addition, from the viewpoint of better exerting the charge neutralization effect of the resin layer, it is preferable that the surface layer does not contain an ionic conductive agent.
[0061] The thickness of the surface layer 41a may be, for example, 100 μm or less, preferably 9 to 70 μm, and more preferably 10 to 50 μm. When the thickness of the surface layer 41a is within the above range, not only is electrostatic offset suppressed, but durability is also improved. In particular, when the thickness of the surface layer is 10 μm or more, durability is further improved. When the thickness of the surface layer is 50 μm or less, the charge neutralizing effect of the resin layer is more easily exerted, and electrostatic offset can be further suppressed.
[0062] The inner surface of the surface layer 41a is preferably hydrophilically treated. The inner surface of the surface layer 41a may be sodium-treated, excimer laser-treated, ammonia-treated, or plasma-etched. The inner surface treatment can improve the adhesiveness. In this embodiment, a PFA tube having a thickness of 20 μm obtained by extrusion molding is used. The inner surface of the tube is hydrophilically treated by plasma etching to improve the wettability with the adhesive described later.
[0063] When the grid part of the corona discharger is arranged so as to have a gap of 10 mm from the outer surface of the electrophotographic member, and then a voltage of -5 kV is applied to the corona discharger for 15.0 seconds, the average potential for 14.0 to 15.0 seconds after the voltage is applied is taken as the surface potential, and the surface potential is preferably -650 V or more. The surface potential is more preferably -650 V to 0 V, even more preferably -650 to -500 V, and even more preferably -620 to -550 V. When the surface potential is within the above range, the charge neutralization effect is more easily exhibited, and the electrostatic offset can be more effectively suppressed. The surface potential can be controlled by the amount of the ion conductive agent, the thickness of the resin layer, and the thickness of the surface layer.
[0064] <Electrophotographic image forming apparatus> 1 is a cross-sectional view of a color electrophotographic printer, which is an example of an electrophotographic image forming apparatus (hereinafter also referred to as an "image forming apparatus") according to the present embodiment, taken along a sheet conveying direction. In this embodiment, the color electrophotographic printer is simply referred to as a "printer."
[0065] The printer 1 shown in FIG. 1 includes image forming units 10 for the colors Y (yellow), M (magenta), C (cyan), and Bk (black). A photosensitive drum (photoconductor) 11 is pre-charged by a charger 12. The photosensitive drum 11 is then exposed by a laser scanner 13 to form an electrostatic latent image. The electrostatic latent image is turned into a toner image by a developer 14. The toner images on the photosensitive drum 11 are sequentially transferred by a primary transfer blade 17 to an image carrier, for example, an intermediate transfer belt 31. After transfer, the toner remaining on the photosensitive drum 11 is removed by a cleaner 15. As a result, the surface of the photosensitive drum 11 becomes clean and is prepared for the next image formation.
[0066] Meanwhile, recording materials (sheets) P are sent out one by one in the direction of arrow 3 from a paper feed cassette 20 or a multi-paper feed tray 25 to a pair of registration rollers 23. The pair of registration rollers 23 temporarily receives the recording material P and straightens it out if it is skewed. The pair of registration rollers 23 then synchronizes with the toner image on the intermediate transfer belt 31 and sends the recording material P between the intermediate transfer belt 31 and a secondary transfer roller 35. The color toner image on the intermediate transfer belt is transferred onto the recording material P by a transfer body such as the secondary transfer roller 35. The toner image on the recording material P is then fixed onto the recording material P by being heated and pressed by a fixing device 40.
[0067] The fixing device 40 includes a fixing member and a pressure member disposed opposite the fixing member. Fig. 2 is a schematic diagram of the fixing device 40, and shows an example of a film heating type heating device (tensionless type). This embodiment uses such a heating device, but a roller pair type or film type heating device can also be used.
[0068] Reference numeral 43 denotes a ceramic heater (hereafter referred to as heater) as a heating element. The heater 43 is basically composed of a long, thin ceramic substrate with its longitudinal direction perpendicular to the drawing, and an energized heat generating resistor layer provided on the surface of the substrate. The heater 43 is a low-heat capacity heater that increases in temperature with a steep rise characteristic overall when electricity is applied to the heat generating resistor layer. It is also configured to switch the energized area depending on the longitudinal width size of the recording material.
[0069] An electrophotographic member according to at least one embodiment of the present disclosure can be used as a fixing member, for example. A specific embodiment of the fixing member is a fixing belt 41 shown in FIG. 3. The fixing belt 41 is a heat-resistant fixing member having a cylindrical shape (endless shape) as a heating member that transmits heat, and is loosely fitted on a support member (heater holder) including the heater 43. As shown in FIG. 3, the fixing belt 41 has at least a surface layer 41a, a resin layer 41b, an elastic layer 41c, and a base layer 41d. Other layers may be provided as necessary between the base layer 41d, the resin layer 41b, the elastic layer 41c, and the surface layer 41a, and on the inner peripheral surface side of the base layer 41d.
[0070] The pressure roller 44 is a heat-resistant elastic pressure roller serving as a pressure member, and has a core and an elastic layer made of heat-resistant rubber such as silicone rubber or fluororubber, or a silicone rubber foam. Both ends of the core are rotatably supported by bearings. The electrophotographic member according to at least one aspect of the present disclosure can also be used as a pressure member, for example. In other words, it is preferable that at least one of the fixing member and the pressure member is the electrophotographic member. For example, the pressure member can have the same structure as the fixing belt 41, and the pressure member can also have a four-layer composite structure including a surface layer 41a, a resin layer 41b, an elastic layer 41c, and a base layer 41d. It is possible.
[0071] The fixing belt 41 and heater 43 are disposed above the pressure roller 44 in parallel to the pressure roller 44, and pressed by a pressing member (not shown). In this manner, the lower surface of the heater 43 and the upper surface of the pressure roller 44 are pressed against each other via the fixing belt 41 against the elasticity of the elastic layer, forming a fixing nip portion of a predetermined width as a heating portion.
[0072] The pressure roller 44 is driven to rotate at a predetermined peripheral speed in the counterclockwise direction indicated by the arrow by a driving means (not shown). When the pressure roller 44 is driven to rotate, a rotational force acts on the cylindrical fixing belt 41 due to the frictional force of the pressure contact at the fixing nip between the pressure roller 44 and the fixing belt 41. As a result, the fixing belt 41 is rotated clockwise as indicated by the arrow while sliding in close contact with the lower surface of the heater 43. The support member (heater holder) 46 also serves as a rotation guide member for the fixing belt 41.
[0073] The pressure roller 44 is driven to rotate, and the cylindrical fixing belt 41 is driven to rotate accordingly, and the heater 43 is energized, so that the heater is heated quickly to a predetermined temperature and is in a temperature-regulated state. In this state, the recording material P carrying the unfixed toner image T is introduced between the fixing belt 41 and the pressure roller 44 in the fixing nip. Then, in the fixing nip, the toner image-carrying side of the recording material P is in close contact with the outer surface of the fixing belt 41 and is sandwiched and conveyed to the fixing nip together with the fixing belt 41. During this sandwiching and conveying process, the recording material P is heated by the heat of the fixing belt 41 heated by the heater 43, and the unfixed toner image T on the recording material P is heated and pressed onto the recording material P, so that it is melted and fixed. The recording material P that has passed through the fixing nip is separated from the surface of the fixing belt 41 by curvature and conveyed to be discharged.
[0074] Reference numeral 45 denotes a contact thermometer (thermistor) that measures the temperature of the fixing belt 41 heated by the heater 43 and passes the detection result to a temperature control means (not shown). Reference numeral 46 denotes a heater holder, which is a member that holds the heater 43 that has been heated to a high temperature. EXAMPLES
[0075] The fixing member and the image forming apparatus according to the present disclosure will be described below with reference to examples. Note that the fixing member and the image forming apparatus according to the present disclosure are not limited to the configurations embodied in these examples.
[0076] Example 1 (Electrophotographic Belt Manufacturing Method) Next, a method for producing the electrophotographic belt used in this example will be described. In this example, the electrophotographic belt shown in FIG.
[0077] (Process 1) A base layer having an endless belt shape made of SUS with an inner diameter of 25 mm, a width of 400 mm, and a thickness of 40 μm was prepared as the base layer. A primer layer and an elastic layer were formed on this base layer by the following procedure. A hydrosilyl silicone primer (product name: DY39-051; Dow Toray, equal parts of liquid A and liquid B mixed) was applied onto the base layer and cured by heating for 5 minutes at 200° C. An addition-curing liquid silicone rubber mixture containing the following components (a) to (d) was applied onto the primer layer to a thickness of 250 μm and cured by heating for 30 minutes at 200° C. to form an elastic layer containing silicone rubber and having a thickness of 250 μm.
[0078] (Liquid silicone rubber mixture) Component (a): Linear organopolysiloxane having an unsaturated aliphatic group Component (b): Organopolysiloxane having active hydrogen bonded to silicon Component (c): Catalyst Component (d): Thermally conductive filler
[0079] First, 100 parts by mass of a silicone polymer having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups, was prepared as component (a). This silicone polymer (trade name: DMS-V35, manufactured by Gelest, viscosity 5000 mm 2 / s) will be referred to as "Vi" from here on. Next, 370 parts by mass of alumina (product name: Amina Beads CB-P10, manufactured by Showa Denko K.K.) was added to this Vi as component (d), and the mixture was placed in a planetary mixer (Thinky Corporation, ARV-5000) and stirred and mixed at 600 rpm for 2 minutes to obtain mixture 1.
[0080] Next, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), which is a cure retarder, was dissolved in the same weight of toluene and added to the mixture 1 to obtain a mixture 2. Next, 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) as component (c) was added to mixture 2 to obtain mixture 3. Furthermore, as component (b), a silicone polymer having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chain (product name: HMS-301, manufactured by Gelest, viscosity 30 mm 2 1.1 parts by mass of 1.2 parts by mass of 1.2-hexanediaminetetraacetate (hereinafter referred to as "SiH") was weighed out. This was added to mixture 3 and mixed thoroughly to obtain a liquid silicone rubber mixture. The surface resistance of this elastic layer was measured using the method described in Evaluation 1. The result was 1×10 15 It was Ω / □.
[0081] (Process 2) While rotating the base layer on which the elastic layer was formed at a moving speed of 20 mm / sec in the circumferential direction, the surface of the elastic layer was irradiated with ultraviolet light in an air atmosphere using an ultraviolet lamp disposed at a distance of 10 mm from the surface of the elastic layer. A low-pressure mercury ultraviolet lamp (product name: GLQ500US / 11, manufactured by Toshiba Lighting & Technology Corporation) was used as the ultraviolet lamp, and the integrated light amount of a wavelength of 185 nm on the irradiated surface was 800 mJ / cm. 2 The irradiation was performed so that
[0082] (Step 3) A mixture of 100 parts by mass of addition-curing silicone rubber adhesive (product name: SE1819CV, a mixture of equal amounts of "Liquid A" and "Liquid B" manufactured by Dow Corning Toray Co., Ltd.) and 0.5 parts by mass of an ionic conductive agent having the structure shown in the following formula (1) (product name: FC-4400; manufactured by 3M Japan Ltd.) was applied to the surface of the elastic layer to a thickness shown in Table 1 to form a coating of the mixture. (n-C4H9)3(CH3)N + N -(SO2CF3)2(1)
[0083] On the other hand, a fluororesin (product name: Teflon PFA 959HP-Plus; Mitsui-Chemours Fluoroproducts, Inc.) was cylindrically extruded to produce a fluororesin tube with a thickness of 9 μm. The inner circumferential surface of the obtained fluororesin tube was hydrophilized, and then the fluororesin tube was placed on the coating of the mixed liquid so that the hydrophilized inner circumferential surface of the fluororesin tube was in contact with the coating of the mixed liquid. Then, the fluororesin tube was uniformly squeezed from above to squeeze out excess mixed liquid from between the elastic layer and the fluororesin tube. The obtained laminate was then placed in an electric furnace set at a temperature of 200° C. and heated for 1 hour to cure the coating of the mixed liquid between the elastic layer and the fluororesin tube, thereby fixing the fluororesin tube onto the elastic layer. Then, both ends of the laminate were cut to obtain an electrophotographic belt with a width of 350 mm.
[0084] (Evaluation method) (Evaluation 1: Evaluation of thickness of surface layer, surface resistivity of surface layer, resin layer and elastic layer) First, the surface layer was separated from the electrophotographic belt by the following methods (1) to (3). (1) A razor was inserted between the elastic layer and the base layer, and the elastic layer and the surface layer were peeled off from the base layer. (2) The laminate of the peeled elastic layer and surface layer was immersed in a silicone solvent (product name: eSolb 21RS; manufactured by Kaneko Chemical Co., Ltd.) at a temperature of 40°C, placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves were applied for 60 minutes to dissolve the elastic layer. The silicone solvent contained dodecylbenzene sulfate at a concentration of 10 parts by mass and normal propyl bromide at a ratio of 90 parts by mass. (3) The surface layer was removed from the silicone solvent, washed with water, and then wiped with toluene and then with ethanol.
[0085] The thickness of the surface layer obtained in (3) above was measured using a micrometer (product name: high-precision digital micrometer MDH-25MB; manufactured by Mitutoyo Corporation). The thickness of the surface layer was measured at any five points where the UR-SS probe was applied using a micrometer (high-precision digital micrometer MDH-25MB, manufactured by Mitutoyo Corporation), and the arithmetic average value of the five points was used. The surface resistivity of the surface layer was measured by a method conforming to the Japanese Industrial Standards (JIS) K6911; 2006. Specifically, the measurement was performed using a high-resistance resistivity meter (product name: Hirester UX MCP-HT800; manufactured by Nitto Seiko Analytech Co., Ltd.). The probe was a ring probe ( (Product name: UR-SS; manufactured by Nitto Seiko Analytech Co., Ltd.) was used. A voltage was applied for 20 seconds, and the value obtained by measurement was taken as the surface resistivity.
[0086] The surface resistivity of the elastic layer was measured by the following procedure. A razor was inserted into the interface between the elastic layer and the base layer of the electrophotographic belt, and the base layer was peeled off to prepare a sample consisting of the elastic layer, the resin layer, and the surface layer. The surface resistivity of the surface of the elastic layer of the obtained sample was measured in the same manner as above.
[0087] The surface resistivity of the resin layer was measured by the following procedure. A razor was inserted between the elastic layer and the base layer from the surface of the electrophotographic belt, and the layers were peeled off to prepare a sample. The elastic layer of the obtained sample was scraped off with the razor to expose the surface of the resin layer. The surface resistivity of the exposed surface of the resin layer was measured in the same manner as above.
[0088] (Evaluation 2: Evaluation of surface potential (charged potential)) To measure the charge potential, the charge on the surface of the electrophotographic belt was first removed. Specifically, the surface of the electrophotographic belt was wiped with a nonwoven fabric soaked in ethanol (product name: BEMCOT; manufactured by Ozu Sangyo Co., Ltd.) to remove the charge on the surface. Hereinafter, this operation is also referred to as "surface de-electrification."
[0089] Next, while rotating the electrophotographic belt, the surface of the fixing member was charged by a corona charger, and the charging potential was measured by a surface electrometer. First, as shown in FIG. 4, an electrophotographic belt 502 was fixed to a bearing (not shown), and then a corona discharge grid 501 was arranged so that a gap of 10 mm was formed between the outer surface of the electrophotographic belt of a certain phase (defined as phase A) in a direction perpendicular to the axial direction of the electrophotographic belt. Then, a probe 503 of the surface electrometer was installed so that a gap of 8 mm was formed between the center of the electrophotographic belt in a phase (defined as phase B) rotated 180° in the circumferential direction from phase A and the direction perpendicular to the axial direction of the electrophotographic belt. In this state, the electrophotographic belt was rotated, and measurement was started when the surface potential in the circumferential direction of the electrophotographic belt was ±10 V or less. If it was not ±10 V or less, measurement was started when the surface potential was 10 V or less. The static electricity on the surface was removed again.
[0090] Thereafter, while rotating the electrophotographic belt at 60 rpm, a voltage of -5 kV was applied to the corona charger to charge the surface, and the potential was measured. At this time, the surface potential was obtained at 0.1 second intervals, and the average potential for 14.0 to 15.0 seconds after application of -5 kV by the corona charger was taken as the surface potential (charged potential).
[0091] (Rating 3: Image rating) A full-color copying machine (product name: iR-ADV C3835F; manufactured by Canon Inc.) was prepared as an image forming apparatus. The full-color copying machine was equipped with a fixing device shown in FIG. 2. The electrophotographic belt to be evaluated was installed as a fixing belt in the fixing device, and the following evaluations were performed. The evaluation conditions were as follows. Test environment: Room temperature 25℃, humidity 10%RH Process speed: 150mm / sec Threading conditions; (1) The full-color copier body and the fixing device (including the fixing belt and pressure roller) were all de-ionized using an ionizer. (2) After leaving the paper in the above test environment for 10 days, 100 sheets of A4 size copy paper (product name: CS-068, manufactured by Canon Inc., basis weight: 68 g) were printed in a continuous manner to form a solid white image on one side. (3) Following (2) above, 10 sheets of A4 size copy paper (product name: Office70; manufactured by Canon Inc., basis weight: 70 g) that had been left in the above test environment for 10 days were printed in a continuous manner to form halftone images on the entire surface of both sides. The halftone images formed on both sides of the 10 printed sheets obtained in (3) above were visually observed for the presence or absence of defects due to electrostatic offset, and the results were evaluated according to the following criteria. (Evaluation Criteria) Rank S: No defects due to toner offset were observed in any of the 10 printed sheets. Rank A: Defects due to toner offset were observed on one of ten prints. Rank B: Defects due to toner offset were observed on 3 to 7 of the 10 printed sheets. Rank C: Defects due to toner offset were observed on 8 to 9 of the 10 printed sheets. Rank D: Defects due to toner offset were observed in all 10 printed sheets.
[0092] (Rating 4: Durability rating) The electrophotographic belt thus produced was attached to a fixing device shown in Fig. 2 and evaluated under the following conditions. Test environment: Room temperature 25℃, humidity 50%RH Process speed: 150mm / sec Threading conditions; (1) An image forming operation in which a grid-like image was formed on A4-size copy paper (product name: CS-068; manufactured by Canon Inc., basis weight: 68 g, thickness: 92 μm) was performed until the number of sheets passed reached 800,000. (2) Every time the number of sheets passed continuously in the above (1) reached 100,000 sheets, one halftone image was formed on the entire surface of one side of a copy paper of SRA3 size (product name: GF-C081; manufactured by Canon Inc., basis weight: 81.4 g). The halftone image thus obtained was then visually observed for the presence or absence of defects on the image due to peeling at the interface between the surface layer and the elastic layer, and the results were evaluated according to the following criteria. (Evaluation Criteria) Rank A: No defects were observed in the halftone image formed after the number of sheets passed in the above (1) reached 800,000. Rank B: Defects were observed in the halftone image formed after the number of sheets passed reached 600,000 as described above in (1). Rank C: Defects were observed in the halftone image formed after the number of sheets passed in the above (1) reached 500,000. Rank D: Defects were observed in any of the halftone images formed before the number of sheets passed in the above (1) reached 500,000.
[0093] (Evaluation 5: Measurement of thickness of resin layer and elastic layer) The thickness of the resin layer and the elastic layer was measured as follows. First, a measurement sample having a length of 5 mm, a width of 5 mm, and a thickness of the entire thickness of the electrophotographic belt was cut out from an arbitrary position of the electrophotographic belt. The surface of the obtained sample corresponding to the cross section of the electrophotographic belt in the thickness direction was milled for 4 hours using an ion milling device (product name: IM4000; manufactured by Hitachi High-Technologies Corporation) under conditions of a voltage of 1.5 kV, a swing angle of ±30°, and 30 round trips / min, to clean the observation surface of the sample. Next, the cleaned observation surface was observed at a magnification of 100 times using a confocal microscope (product name: H1200; manufactured by Lasertec Corporation), and the average value of the measurement results of the resin layer and the elastic layer at four different points on the observation surface was calculated.
[0094] (Evaluation 6: Measurement of the content of ionic conductive agent in the resin layer) A sample was taken from the resin layer of the electrophotographic belt, and the sample was subjected to thermogravimetric analysis at 425° C. in an air atmosphere using a thermogravimetric analyzer (TGA851, manufactured by METTLER TOLEDO). In the profile of the measurement time vs. mass loss rate obtained by the thermogravimetric analysis, a linear least squares approximation equation was obtained from the region where the slope was constant and only the silicone rubber in the resin layer was reduced. The intercept of the linear least squares approximation equation was taken as the silicone rubber content (mass%), and the ion conductive agent content (mass%) was calculated as 100-silicone rubber content.
[0095] (Examples 2 to 10) The amount of ion conductive agent blended with respect to the addition curing type silicone rubber adhesive was as shown in Table 1. The thicknesses of the surface layer and the resin layer were as shown in Table 2. Except for the above, electrophotographic belts according to Examples 2 to 10 were produced in the same manner as in Example 1. Then, each of the obtained electrophotographic belts was subjected to Evaluations 1 to 6. Example 11 A fixing belt was produced in the same manner as in Example 1, except that (Step 3) in Example 1 was changed as follows. A mixture (addition-curing silicone rubber adhesive mixture) obtained by mixing 100 parts by mass of addition-curing silicone rubber adhesive (product name: SE1819CV, a mixture of equal amounts of "Liquid A" and "Liquid B" manufactured by Dow Corning Toray Co., Ltd.), 0.25 parts by mass of an ionic conductive agent having the structure shown in formula (1) below (product name: FC-4400; manufactured by 3M Japan Ltd.) and 0.25 parts by mass of an ionic conductive agent containing a cation having a siloxane bond in the molecule (product name: X-40-2750; manufactured by Shin-Etsu Chemical Co., Ltd.) was applied to the surface of the elastic layer to a thickness shown in Table 1 to form a layer of the mixture. (n-C4H9)3(CH3)N + N - (SO2CF3)2(1)
[0096] Comparative Example 1 In the manufacturing method of the fixing belt in Example 1, the fixing belt was manufactured by adding 1% by mass of carbon particles to the fluororesin tube.
[0097] Comparative Example 2 An electrophotographic belt was produced in the same manner as in Example 1, except that in the manufacturing method of the fixing belt in Example 1, 30% by mass of carbon black (product name: Denka Black, manufactured by Denka Co., Ltd.) was added to the elastic layer.
[0098] Comparative Example 3 In the manufacturing method of the fixing belt of Example 1, an addition-curing silicone rubber adhesive containing no ion conductive agent but carbon black was used to form a resin layer (adhesive layer) corresponding to the resin layer. Specifically, 0.5 parts by mass of carbon black (product name: Denka Black; manufactured by Denka Co., Ltd.) was added to 100 parts by mass of an addition-curing silicone rubber adhesive (product name: SE1819CV, manufactured by Dow-Toray, equal amounts of "liquid A" and "liquid B" mixed) to prepare an adhesive according to this comparative example. An electrophotographic belt was manufactured in the same manner as in Example 1, except that this adhesive was used to form the adhesive layer.
[0099] Comparative Example 4 A fixing belt was produced in the same manner as in Example 1 except that the ion conductive agent was not added in step 3.
[0100] Comparative Example 5 An electrophotographic belt was produced in the same manner as in Example 1, except that the amount of the ion conductive agent was changed to 50.0 parts by mass in (Step 3) of Example 1.
[0101] Table 1 shows the thickness of the resin layer and the amount of the ion conductive agent added for the fixing belts produced in Examples 1 to 10 and Comparative Examples 1 to 5. Tables 2 and 3 show the evaluation results of the electrophotographic belts according to Examples 1 to 10 and Comparative Examples 1 to 4.
[0102] [Table 1]
[0103] [Table 2] In Table 2, entries such as "1E+15" are equivalent to "1×10 15 " means.
[0104] [Table 3] In Table 3, "*" means that black spots were observed in the evaluated image in the image evaluation.
[0105] In this way, when the fixing belts produced by the methods described in Examples 1 to 10 were used, it was possible to obtain fixing belts that could prevent electrostatic offset and had high durability. Note that, in Examples 3 and 4, although the content of the ion conductive agent in the resin layer was made higher than that in the resin layer of Example 1, the surface resistivity of the resin layer was the same, but the reason for this is unclear. Next, regarding Comparative Examples 1 and 2, the reason why black dots were observed in the evaluation images in the result of Evaluation 3 is believed to be that conductive leakage occurred due to the aggregated parts of carbon black in the surface layer and the elastic layer. Also, in the electrophotographic belt according to Comparative Example 3, the conductivity of the adhesive layer was due to carbon black, so it is believed that no polarization of charge occurred in the adhesive layer. In other words, it is believed that electrostatic offset occurred because the charge neutralization effect due to the polarization of the ion conductive agent in the resin layer did not occur.
[0106] Furthermore, in Comparative Example 4, the adhesive layer did not contain an ion conductive agent, and therefore the adhesive layer had no charge neutralization effect, which is thought to be why electrostatic offset occurred. Furthermore, in Comparative Example 5, since the resin layer contained a large amount of an ion conductive agent, the surface resistivity of the resin layer was lower than that of the resin layer in the electrophotographic belt according to Example 1. Therefore, the evaluation rank of the electrostatic offset was rank "A". However, the adhesive strength of the resin layer as an adhesive layer was low, and the surface layer peeled off from the elastic layer early during evaluation in rating 4. Therefore, the durability rating was ranked "D".
[0107] The present disclosure relates to the following configurations. (Configuration 1) An electrophotographic member having at least a base layer, an elastic layer, and a surface layer containing a fluororesin, in that order, The surface resistivity of the elastic layer is 1×10 14 Ω / □ or more, The surface resistivity of the surface layer is 1×10 15 Ω / □ or more, the electrophotographic member further comprises a resin layer between the elastic layer and the surface layer, The resin layer contains an ion conductive agent, and The surface resistivity of the resin layer is 1×10 14 Electrophotographic member having a resistivity of Ω / □ or more. (Configuration 2) The electrophotographic member according to Constitution 1, wherein a grid part of a corona discharger is disposed so as to have a gap of 10 mm from the outer surface of the electrophotographic member, and then a voltage of -5 kV is applied to the corona discharger for 15.0 seconds; when the average potential for 14.0 to 15.0 seconds after the application of the voltage is taken as the surface potential, the surface potential is -650 V or more. (Configuration 3) 3. The electrophotographic member according to configuration 1 or 2, wherein the content of the ion conductive agent in the resin layer is 1.0 to 30.0 parts by mass with respect to 100 parts by mass of the resin. (Configuration 4) 4. The electrophotographic member according to any one of configurations 1 to 3, wherein the resin layer has a thickness of 0.5 to 5.0 μm. (Configuration 5) 5. The electrophotographic member according to any one of configurations 1 to 4, wherein the surface layer has a thickness of 10 to 50 μm. (Configuration 6) 6. The electrophotographic member according to any one of configurations 1 to 5, wherein the fluororesin contains a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer. (Configuration 7) 7. The electrophotographic member according to any one of configurations 1 to 6, wherein the elastic layer contains a cured product of an addition-curing type liquid silicone rubber mixture. (Configuration 8) 8. The electrophotographic member according to any one of configurations 1 to 7, wherein the resin layer is a cured product of an addition-curing type silicone rubber adhesive mixture containing the ion conductive agent and an addition-curing type silicone rubber adhesive. (Configuration 9) 9. The electrophotographic member according to any one of configurations 1 to 8, wherein the ionic conductive agent contains a cation having a siloxane bond in the molecule, and contains at least one anion selected from the group consisting of TFSI and FSI. (Configuration 10) 10. The electrophotographic member according to any one of Configurations 1 to 9, wherein the surface layer does not contain an electronic conductive agent or an ionic conductive agent. (Configuration 11) 11. The electrophotographic member according to any one of configurations 1 to 10, wherein the electrophotographic member is an electrophotographic belt having an endless shape. (Configuration 12) 12. The electrophotographic member of embodiment 11, wherein the electrophotographic member is a fuser belt. (Configuration 13) A fixing device in an electrophotographic image forming apparatus, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. A fixing device, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 12. (Configuration 14) An electrophotographic image forming apparatus including a fixing device, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. An electrophotographic image forming apparatus, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 12.
[0108] 10: image forming unit, 11: photosensitive drum, 12: charger, 13: laser scanner, 14: developer, 15: cleaner, 17: primary transfer blade, 20: paper feed cassette, 25: multi-paper feed tray, 23: registration roller pair, 31: intermediate transfer belt, 35: secondary transfer roller, 40: Fixing unit, 41: Fixing belt, 41a: Surface layer, 41b: Adhesive layer (resin layer), 41c: Elastic layer, 41d: Base layer, 43: Heating body, 44: Pressure roller, 45: Contact type thermistor, 46: Heater holder, 501: Corona discharge grid, 502: Fixing member, 503: Probe of surface potential meter, P: Recording material, T: Toner
Claims
1. An electrophotographic member having at least a base layer, an elastic layer, and a surface layer containing a fluororesin, in that order, The surface resistivity of the elastic layer is 1×10 14 Ω / □ or more, The surface resistivity of the surface layer is 1×10 15 Ω / □ or more, the electrophotographic member further comprises a resin layer between the elastic layer and the surface layer, The resin layer contains an ion conductive agent, and The surface resistivity of the resin layer is 1×10 14 Ω / □ or more.
2. 2. The electrophotographic member according to claim 1, wherein a grid part of a corona discharger is disposed so as to have a gap of 10 mm from the outer surface of the electrophotographic member, and then a voltage of -5 kV is applied to the corona discharger for 15.0 seconds, and when an average potential for 14.0 to 15.0 seconds after application of the voltage is taken as the surface potential, the surface potential is -650 V or more.
3. 2. The electrophotographic member according to claim 1, wherein the content of the ion conductive agent in the resin layer is 1.0 to 30.0 parts by weight per 100 parts by weight of the resin.
4. 2. The electrophotographic member of claim 1, wherein the resin layer has a thickness of from 0.5 to 5.0 μm.
5. 2. The electrophotographic member of claim 1, wherein said surface layer has a thickness of from 10 to 50 μm.
6. 2. The electrophotographic member of claim 1, wherein said fluororesin comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer.
7. 2. An electrophotographic member according to claim 1, wherein said elastic layer comprises a cured product of an addition-curing type liquid silicone rubber mixture.
8. 2. The electrophotographic member of claim 1, wherein said resin layer is a cured product of an addition cure type silicone rubber adhesive mixture containing said ion conductive agent and an addition cure type silicone rubber adhesive.
9. 9. The electrophotographic member of claim 8, wherein said ionic conductive agent contains a cation having a siloxane bond in the molecule and at least one anion selected from the group consisting of TFSI and FSI.
10. 2. The electrophotographic member of claim 1, wherein said surface layer is free of electronic and ionic conductive agents.
11. 2. The electrophotographic member of claim 1 wherein said electrophotographic member is an electrophotographic belt having an endless configuration.
12. 12. The electrophotographic member of claim 11, wherein said electrophotographic member is a fuser belt.
13. A fixing device, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, A fixing device, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of claims 1 to 12.
14. An electrophotographic image forming apparatus including a fixing device, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. An electrophotographic image forming apparatus, wherein at least one of said fixing member and said pressure member is the electrophotographic member according to any one of claims 1 to 12.
Citation Information
Patent Citations
Fixing device for electrophotographic device
JP1996220907A
Cited By
Fixing member, method for manufacturing a fixing member, fixing apparatus, and image forming apparatus
JP2026126964A
Fixing apparatus and image forming apparatus
JP2026126969A
Fixing apparatus and image forming apparatus
JP2026126972A
Fixing member, method for manufacturing a fixing member, fixing apparatus, and image forming apparatus
JP7927893B2
Fixing member, method for manufacturing a fixing member, fixing apparatus, and image forming apparatus
JP7934085B1